Correlation Between Plasma Endothelin-1, Blood Glucose and Serum Calcium in Male Rats Instillated with Bleomycin - MAULOOD, ISMAIL M.; JAF, HAMA NAJM H.; MAHMUD, ALMAS M. R. (Science Journal of University of Zakho, 2013)
Endothelin-1 is profibrotic by stimulating fibroblast replication, migration, contraction, collagen synthesis and secretion while decreasing collagen degradation.In the present study,20male rats weighing 240 grams and 10-12 weeks old were utilized.Pulmonary fibrosis was induced by a single instillation of bleomycin (90 mg/kg).After 7 days of instillation, elevated plasma ET-1 was considered as bleomycin induced pulmonary fibrosis. High dose of bleomycin instillation caused significant increase in plasma ET-1as compared with normal saline instillation. Blood glucose and serum calcium were also markedly elevated. Statistical analysis using Pearson coefficient of correlation revealed that there was a positive relationship between plasma ET-1 and blood sugar (r=0.7). The same correlation was detected between plasma ET-1 and serum calcium (r=0.7).The present study concluded thatthere is a strong correlation between plasma ET-1 and blood glucose and it may be due to decreaseof insulinsensitivity, and inhibits β-cells to release insulin .In addition,the role of calcium ions cannot be excluded in raising blood glucose by ET-1.